2021
DOI: 10.1097/aln.0000000000003899
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Rivaroxaban Anticoagulation as Part of a Multimodal Hemostatic Intervention in a Polytrauma Animal Model

Abstract: Background Life-threatening bleeding requires prompt reversal of the anticoagulant effects of factor Xa inhibitors. This study investigated the effectiveness of four-factor prothrombin complex concentrate in treating trauma-related hemorrhage with rivaroxaban-anticoagulation in a pig polytrauma model. This study also tested the hypothesis that the combined use of a low dose of prothrombin complex concentrate plus tranexamic acid and fibrinogen concentrate could improve its subtherapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In contrast, a correlation between thrombin generation improvement and bleeding correction was evident in a similar study with edoxaban‐anticoagulated individuals 15 . Also, in an animal bleeding model of rivaroxaban‐treated pigs that underwent complex traumatic injury followed by PCC treatment, correction of hemostasis coincided with improvement of thrombin generation 30 . In the same polytrauma model, andexanet alfa rapidly restored thrombin generation and significantly reduced total blood loss in apixaban‐treated animals 31 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, a correlation between thrombin generation improvement and bleeding correction was evident in a similar study with edoxaban‐anticoagulated individuals 15 . Also, in an animal bleeding model of rivaroxaban‐treated pigs that underwent complex traumatic injury followed by PCC treatment, correction of hemostasis coincided with improvement of thrombin generation 30 . In the same polytrauma model, andexanet alfa rapidly restored thrombin generation and significantly reduced total blood loss in apixaban‐treated animals 31 .…”
Section: Discussionmentioning
confidence: 83%
“… 15 Also, in an animal bleeding model of rivaroxaban‐treated pigs that underwent complex traumatic injury followed by PCC treatment, correction of hemostasis coincided with improvement of thrombin generation. 30 In the same polytrauma model, andexanet alfa rapidly restored thrombin generation and significantly reduced total blood loss in apixaban‐treated animals. 31 We observed in our in vitro experiments that andexanet alfa increased peak thrombin and velocity index to above normal, irrespective of the presence of FXaI.…”
Section: Discussionmentioning
confidence: 95%
“…In vitro data showed that idarucizumab reduced plasma concentrations of dabigatran ( 143 ) and that andexanet alfa lowered the concentrations of FXa-inhibitors but did not normalize VEM ( 143 ). In a porcine trauma model, PCC effectively reduced blood loss, restored haemostasis, and balanced thrombin generation despite previous rivaroxaban intake ( 144 ). However, outcome data remain inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…The authors administered increasing doses of prothrombin complex concentrate (PCC; 12.5, 25, and 50 U/kg) along with combinations of PCC plus tranexamic acid and fibrinogen concentrate, and determined total blood loss and survival over 4 h. In comparison to controls (saline), treatment with PCC 25 and 50 U/kg and PCC 12.5 U/kg plus tranexamic acid and fibrinogen concentrate reduced bleeding and achieved 100% survival versus 0% in controls. 1 The important findings of this study include the following. First, the impact of a high rivaroxaban plasma concentration on rotational thrombelastometry (ROTEM) showed a prolonged extrinsically activated clotting time, while maximum clot formation was unaltered.…”
mentioning
confidence: 86%
“…In this issue of the Journal, the article by Rayatdoost et al provides novel data from an established polytrauma pig model. 1 In brief, a high rivaroxaban plasma concentration (approximately 400 ng/ ml) was established in anesthetized pigs before inflicting a standardized major trauma of blunt liver injury and bilateral femur fractures. The authors administered increasing doses of prothrombin complex concentrate (PCC; 12.5, 25, and 50 U/kg) along with combinations of PCC plus tranexamic acid and fibrinogen concentrate, and determined total blood loss and survival over 4 h. In comparison to controls (saline), treatment with PCC 25 and 50 U/kg and PCC 12.5 U/kg plus tranexamic acid and fibrinogen concentrate reduced bleeding and achieved 100% survival versus 0% in controls.…”
mentioning
confidence: 99%